1999
DOI: 10.1097/00006534-199902000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Cleft Palate: I. Characterization of a Congenital Model

Abstract: Any animal model of a human congenital anomaly established by iatrogenic methods involving intrauterine fetal manipulation has limited clinical applicability. A congenital model that more closely simulates the etiopathogenesis of a human anomaly may provide data that can more readily be extrapolated to that anomaly and, therefore, be used in diagnostic and management strategies. The present work provides a description and characterization of a congenital model of cleft palate in the goat. Palatal shelf closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Under these circumstances, the fibers of the cleft palate might not have been exposed to the appropriate environmental cues to convert to or to maintain mature slow type 1 fibers. Loading abnormalities were possible during the induction of the cleft palate when the fetal neck was hyper-flexed and the tongue was wedged between the palatal shelves (Weinzweig et al, 1999). Following the induction of the cleft, atypical loading persisted in that the LVP muscle fibers were abnormally attached to the posterior edge of the palatal bone and, consequently, were exposed to forces along the posterior-anterior direction rather than the medial-lateral orientation of normal palatal LVP fibers (Weinzweig et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these circumstances, the fibers of the cleft palate might not have been exposed to the appropriate environmental cues to convert to or to maintain mature slow type 1 fibers. Loading abnormalities were possible during the induction of the cleft palate when the fetal neck was hyper-flexed and the tongue was wedged between the palatal shelves (Weinzweig et al, 1999). Following the induction of the cleft, atypical loading persisted in that the LVP muscle fibers were abnormally attached to the posterior edge of the palatal bone and, consequently, were exposed to forces along the posterior-anterior direction rather than the medial-lateral orientation of normal palatal LVP fibers (Weinzweig et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The cleft palate was induced by gavaging pregnant goats with an extract of Nicotiana glauca plant slurry twice daily from day 32 to 41 of gestation, the critical developmental period when palatal shelf closure occurs (Weinzweig et al, 1999). As a consequence, the neck of the fetal goat remained hyperflexed and caused the tongue to obstruct the closure of the palatal shelves resulting in complete clefts of the secondary palates (Weinzweig et al, 1999). Each goat was sacrificed using an overdose of Beuthanasia (Schering-Plough Animal Health Corp., Kenilworth, NJ).…”
Section: Animal Modelmentioning
confidence: 99%
“…There are two important fi ndings that distinguish these agents from that of sulfoxafl or. Ultrasound studies using a goat model demonstrate decreased or eliminated fetal activity when the mother goat is fed anabasine (Weinzweig et al 1999) that was associated with the observed muscle contractures, as well as cleft palate presumably resulting from inactive glossal muscle during palate closure. While the MoA of the plant alkaloids on the fetus is not known, it could be speculated that the previously noted sedation or biphasic stimulation-depression seen in adults may be operant in the fetus and responsible for the inhibition of fetal movement.…”
Section: Fetal-type Muscle Nachr Inactivationmentioning
confidence: 97%
“…During gestational days 32 to 41 (palatal fusion occurs at gestational day 38), cleft palates were induced by gavaging pregnant goats with an extract of Nicotiana glauca plant slurry twice daily (Panter and Keeler, 1992;Weinzweig et al, 1999). The extract causes the neck of the fetal goat to remain hyperflexed, thereby causing the tongue to elevate and obstruct the migration of the palatal shelves to the midline.…”
Section: Congenital Cleft Palate Modelmentioning
confidence: 99%
“…The extract causes the neck of the fetal goat to remain hyperflexed, thereby causing the tongue to elevate and obstruct the migration of the palatal shelves to the midline. Thus, palatal fusion is physically inhibited in 97% of cases, with complete clefting of the secondary palate in all cases (Weinzweig et al, 1999). …”
mentioning
confidence: 99%